Peer and tutor interaction effects on collaborative learning: The role of learning self-efficacy - Intaratat, Kamolrat; Osman, Zahir; Thi Nguyen, Huong-An; Dwi Jayanti Suhandoko, Astri; Sultana, Naveed (Edelweiss Applied Science and Technology, 2024)
This study delves into the intricate relationships among individual work performance, learning self-efficacy, and collaborative learning within the context of online distance learning in higher education institutions. Quantitative research methodology, focusing on students enrolled in online distance-learning programs at higher education institutions in Thailand. Data was primarily collected through a survey questionnaire, using established measurement instruments to assess key constructs includes 16 variables from 223 samples. The Structural Equation Modeling (SEM) was employed to examine complex relationships between variables then analysed by the Smart-PLS 4 software. Findings reveal significant positive associations, supported by robust statistical evidence and effect size analyses. The study contributes to theoretical frameworks by emphasizing the sequential impact of individual work factors on collaborative learning, mediated by learning self-efficacy. Practical implications are evident for educators, administrators, and instructional designers, highlighting the importance of fostering a sense of community, leveraging technology, and building students' self-efficacy beliefs. For future research, including longitudinal studies and investigations into contextual influences. Overall, this study enhances our understanding of the dynamics in online education, offering valuable insights with implications for both theory and practice in the evolving landscape of virtual higher education.